Blockchain security for 5G network using Internet of Things devices - Khalifa, Othman Omran; Ahmed, Muhammed Zaharadeen; Saeed, Rashid A.; Hussaini, Saleh; Hassan Abdalla Hashim, Aisha; El-Khazmi, Elmahdi A. (Institute of Electrical and Electronics Engineers Inc., 2022)
Network of vehicles using Internet of Things (IoT) frameworks have efficient characteristics of modern intelligent transportation system with a few challenges in vehicular ad-hoc networks (VANETs). However, its security framework is required to manage trust management by preserving user privacy. Wireless mobile communication (5G) system is regarded as an outstanding technology that provide ultra-reliable with limited latency wireless communication services. By extension, integrating Software Defined Network (SDN) with 5G-VANET enhances global information gathering and network control. Therefore, real-time IoT application for monitoring transport services is efficiently supported. These ensures vehicular security on this framework. This paper provides a technical solution to a self-confidential framework for a smart transport system. This process exploiting IoT for vehicle communication by incorporating SDN and 5G technology. Due to some features of blockchain, this framework has been implemented to provide various alternative support for vehicular smart services. This involves real-time access to cloud to stream video information and protection management to vehicular network. The implemented framework presents a promising technique and reliable vehicular IoT environment while ensuring user privacy. Results of simulation presents that vehicular nodes/messages (malicious) and overhead is detected and the impact on network performance are satisfactory when deployed in large-scale network scenarios.